Spatio-temporal patterns of an invasive species Mimosa bimucronata (DC.) Kuntze under different climate scenarios in China - Xie, Chunping; Li, Meng; Jim, C. Y.; Liu, Dawei (Frontiers in Forests and Global Change, 2023)
Invasive alien plants pose a serious threat to native ecosystems and their biodiversity. To control their spread and damage, it is critical to clarify the potential distribution patterns of the invaders at the regional scale and their response to climate change. Mimosa bimucronata (DC.) Kuntze, a shrub extremely tolerant of stressful habitat conditions, is used as firewood and hedgerow in the tropics. Since its introduction to China in the 1950s, it has established a sustainable population and become an aggressive invasive species. Due to serious ecological threats in South China, it has been listed as a Key Management Invasive Alien Species. To understand its invasibility in China, two species distribution models, BIOCLIM and DOMAIN, were employed to evaluate the main environmental factors regulating its geographical distribution under the current climate and a future climate change scenario with double CO2 concentration. We found an extensive spread of current suitability habitats in South China, concentrated mainly in the tropical-subtropical provinces of Guangdong, Guangxi, Hainan, and Fujian. The complex interplay of local bioclimatic factors shaped the species distribution. Under the current climate, the predicted range was somewhat larger than the current one. Under the climate change scenario, suitable habitats for Mimosa bimucronata would remain similar to the current one. However, its invasiveness in the current biogeographical range would be more serious. The suitability habitats would expand and shift to the southeastern coastal and northern parts of South China under future climate change. We suggest adopting early monitoring and eradication measures in potential invasion areas and practical measures to contain its spread. The results could provide a conceptual basis to formulate prevention and control strategies to improve future containment of its invasion.